Point prevalence of penicillin allergy in hospital inpatients. Issue 1 (September 2020) - Baxter, M.; Bethune, C.; Powell, R.; Morgan, M.
Summary: Ten percent of the general population believe themselves to be allergic to beta-lactams, many erroneously. Alternative, broader-spectrum antibiotics are associated with increased drug costs and colonization with resistant organisms. A point prevalence study of hospital inpatients determined the local reported rate of penicillin allergy, the nature of allergy described, evidence of antimicrobial resistance and antimicrobial regimens used as a result. Of the 583 patients assessed, the overall rate of penicillin allergy was 13.7% [95% confidence interval (CI) 11–17%]. Rash was the most commonly reported reaction (27.5%, 95% CI 18–39%). Details of the nature of the penicillin allergy were poorly recorded on drug charts. Significantly higher rates of meticillin-resistant Staphylococcus aureus were seen in the allergic cohort ( P =0.0065) compared with those without a label of penicillin allergy; this was also seen for vancomycin-resistant enterococci, but this did not reach significance. This study demonstrates an increase in detection of resistant organisms in penicillin-allergic patients which may result from use of broader-spectrum antibiotics in this group.